2015
DOI: 10.1177/0956462415581125
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of anal sex roles among Malay and Chinese MSM in Kuala Lumpur, Malaysia

Abstract: Identifying roles for anal sex is an important issue for populations of MSM. We describe the prevalence of identifying as being 'top', 'bottom', 'versatile', or 'don't know/not applicable' among Malay and Chinese MSM in Kuala Lumpur, Malaysia, and behavioural outcomes according to these labels for sexual role identity. Data analysis was conducted on a survey administered during weekly outreach throughout Kuala Lumpur in 2012. Pearson's Chi square tests were used to compare demographic and behavioural character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…MSM with “1” roles are dominant during sexual activity and also have a greater sense of self-protection and competence [ 30 , 31 ]. As a result, they tend to be more active in HIV testing [ 32 ]. Lack of awareness of and familiarity with “ChaBei” in the community was a main barrier to MSM recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…MSM with “1” roles are dominant during sexual activity and also have a greater sense of self-protection and competence [ 30 , 31 ]. As a result, they tend to be more active in HIV testing [ 32 ]. Lack of awareness of and familiarity with “ChaBei” in the community was a main barrier to MSM recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, RAI is common worldwide [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Up to 81% of cisgender gay and bisexual men 10 , 20-46% of cisgender women 10,28 (including cisgender heterosexual 29 , lesbian 30 and bisexual 30 women), 80% of transgender women (or transfeminine people) 31,32 and 28% of transgender men (or transmasculine people) 33 engage in RAI.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have used self-reported surveys to measure condom use and PrEP adherence [12][13][14][15], but recall bias affected the accuracy when participants were asked to recall how many times they used condoms or took PrEP over a long period. Some studies asked participants whether they used condoms during the last anal sex event to reduce the recall bias [16][17][18], but a one-time sex event neither reflects the long-term decision-making of condom use nor assesses the longitudinal change of PrEP adherence. Although self-reporting bias is still inevitable, using a website survey or mobile apps to measure condom and PrEP use can be more immediate than traditional surveys [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, having sex with an older partner was more likely to involve condomless anal sex [24]. MSM who identified as bottoms were less likely to use condoms than those identified as tops [18]. MSM were more likely to practice condomless anal sex with a partner whose HIV status was the same as themselves, compared with those who had sex with a partner whose HIV status was different [25].…”
Section: Introductionmentioning
confidence: 99%